21st Century Skills - Perception of College Students Towards e-learning - Dheesha, J.B. (Indian Journal of Educational Technology, 2022)
Digital education is an innovative approach in the present education era. E-learning is known as the use of digital tools, devices and technologies in the teaching-learning process. It depends upon the technological devices, applications and internet facility. Different kinds of educational platforms and tools are available, which are used by the teacher to deliver the content through online learning. The objective of this present study is to find out the perception of college students on e-learning, particularly skills required for 21st century learners. 109 students studying in UG and PG programmes were selected as samples. A questionnaire was used to find out the perception of e-learning among the samples. The study results revealed that the samples are having good perception of e-learning. They also shared that the skills such as communication skills, presentation skills, critical thinking, technical skill and time management are improved through e-learning.